Estimation of wettability of topical fluoride gel on anterior and posterior teeth: An in vitro study - Kiran Srinivas; S Balaji Ganesh; S Jayalakshmi (Wolters Kluwer Medknow Publications, 2022)
The surface area determination has a vital role in measuring the properties of liquid and solid substances. Fluoride is a potent remineralizing agent of the teeth. The surface area is measured using a goniometer. The main aim of this study is to estimate the wettability of topical fluoride gel on the anterior and posterior teeth surfaces. Topical acidulated phosphate fluoride (APF) gel was taken in small quantities. Anterior and posterior teeth were collected, and their superficial unaltered enamel sections were used as the surface where the contact angle (CA) is determined. The surface wettability is determined using Ossila goniometer to measure CA. Each stage was mounted on a mechanical stage of the goniometer. A calibrated microsyringe was used to dispense drops of the APF gel over the surface of the specimen Group A (anterior tooth cut section) and Group B (posterior tooth cut section). This procedure is repeated for all specimen samples. The mean of CAs of the anterior teeth (88.41°) was greater when compared with the mean of posterior teeth (80.36°) CA. P value found using the paired t-test of SPSS software is found to be 0.271 (>0.05), hence statistically not significant. The greater the CA, the lower is the degree of wettability on the teeth surfaces. The mean CA of the topical fluoride APF gel on the anterior tooth surface is greater when compared to the posterior tooth surface. This signifies that greater wettability is seen on posterior tooth surfaces.